Interactive Effect of Gender, Test Anxiety, and Test Items Sequencing on Academic Performance of SS3 Students in Mathematics in Calabar Education Zone, Cross River State, Nigeria - Owan, Valentine J.; Bassey, Bassey A.; Etuk, Ini S. (American Journal of Creative Education, 2020)
The rationale of this study was to examine the interactive effect of gender, test anxiety, and test items sequencing on the academic performance in mathematics among SS3 students in Calabar Education Zone, Cross River State. Two formulated null hypotheses directed the study. The study adopted the quasi-experimental design. Simple random sampling technique was used in drawing a sample of 474 students from a population of 8,549 SS3 students. A Mathematics Achievement Test (MAT) and a Test Anxiety Scale (TAS) were used primarily as the instruments for data collection. The reliability coefficient obtained for both instruments were .88 and .82 respectively. The data collected were analyzed using descriptive statistics such as mean and standard deviation, while the null hypotheses were tested respectively, using Pearson product-moment Correlation, and Analysis of Covariance where applicable. Findings indicated that test anxiety contributes negatively to academic performance in Mathematics; there is a significant interaction effect between item sequencing and gender on academic performance; between item sequencing and test anxiety on academic performance; and between gender and test anxiety on academic performance in Mathematics respectively; The findings also showed that Based on these findings conclusion and recommendations were made.